Damage Mechanism of Mineral Admixture Concrete under Marine Corrosion and Freezing-Thawing Environment - Yan Li; Lianying Zhang; Chao Ma; Bing Li; Jiong Zhu (Advances in Civil Engineering)
Understanding the performance of concrete in the marine environment is significant for preventing the corrosion of chloride ion for marine buildings. In this study, the uniaxial compressive strength (UCS), chloride ion concentration (CIC), microstructure, and pore structure of admixture concretes were tested to study the mechanical properties and microscopic characteristics under the single marine corrosion, the single freezing-thawing, and the coupled marine corrosion and freezing-thawing conditions. The results indicate that the concrete mixed with both fly ash and mineral powder has better UCS, chloride ion penetration resistance, and freezing-thawing resistance than the concrete with the single fly ash or mineral powder. Under the marine corrosion environment and coupled corrosion and freezing-thawing environment, the UCS of the concrete with both fly ash and mineral powder increases firstly and then decreases with the increase of the corrosion time. This is because the pore of the filling body is filled by large crystalline salts generated by the reaction of chloride ions and concrete; then, cementation of the cement is increased in the early corrosion; meanwhile, the increase of crystal salt in the subsequent corrosion process leads to the growth of microcracks and the formation of macrocracks in concrete specimens. In addition, a freezing-thawing-corrosion composite strength impact factor is introduced to describe the effect of coupled corrosion and freezing-thawing on the mechanical property of the concrete. The results show that the corrosion is the dominant factor after 0, 30, and 60 freezing-thawing cycles, while the freezing-thawing is the dominant factor after 90 freezing-thawing cycles.